2012
DOI: 10.1209/0295-5075/99/18001
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of the Bose-Hubbard model on complex networks

Abstract: -Critical phenomena can show unusual phase diagrams when defined in complex network topologies. The case of classical phase transitions such as the classical Ising model and the percolation transition has been studied extensively in the last decade. Here we show that the phase diagram of the Bose-Hubbard model, an exclusively quantum mechanical phase transition, also changes significantly when defined on random scale-free networks. We present a mean-field calculation of the model in annealed networks and we sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…In fact it was shown that the classical Ising model [18][19][20], the percolation transition [21] the epidemic spreading [22] change significantly when the second moment k(k − 1) of the degree distribution diverges. Recently it is becoming clear that these effects of the topology apply also to quantum critical phenomena [23] and are found in the mean-field solution of both the Random Transverse Ising Model [15] and the Bose-Hubbard model [24]. An open problem, that we approach in this paper is to what extent mean-field results are indicative of the behavior of the critical phenomena in quenched networks.…”
Section: Introductionmentioning
confidence: 89%
“…In fact it was shown that the classical Ising model [18][19][20], the percolation transition [21] the epidemic spreading [22] change significantly when the second moment k(k − 1) of the degree distribution diverges. Recently it is becoming clear that these effects of the topology apply also to quantum critical phenomena [23] and are found in the mean-field solution of both the Random Transverse Ising Model [15] and the Bose-Hubbard model [24]. An open problem, that we approach in this paper is to what extent mean-field results are indicative of the behavior of the critical phenomena in quenched networks.…”
Section: Introductionmentioning
confidence: 89%
“…Complex networks model systems as diverse as the brain and the internet; however, up till now they have been obtained in quantum systems by explicitly enforcing complex network structure in their quantum connections [2][3][4][5][6][7], e.g. entanglement percolation on a complex network [4].…”
mentioning
confidence: 99%
“…However, at the most basic level we can first ask, are quantum systems inherently complex? Must we impose complexity on quantum systems to obtain it [2][3][4][5][6][7], or is there a regime in which complexity naturally emerges, even in ground states of regular lattice models? In this Letter we show that emergent complexity can be well quantified in the simplest of 1D lattice quantum simulator models in terms of complexity measures around QCPs in direct analogy to similar measurements on the brain; moreover we establish a much-needed new set of tools for quantifying the complexity of far-from-equilibrium quantum dynamics.…”
mentioning
confidence: 99%
“…Extensive research has been addressed to the characterization of quantum walks on complex networks (see Figure 4) [41,42,50] and to quantum transport [108]. Other critical phenomena studied on networks are the quantum Ising model, the Bose Hubbard model, Anderson localization, Bose-Einstein condensation between others [43][44][45][46][47][48][49]. It has been found that network structure strongly affect the phase diagram of quantum dynamical processes.…”
mentioning
confidence: 99%